Digital Translanguaging in EFL Learning: A Systematic Literature Review - Rudiaman Purba; Rudi Hartono; Yuliati (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This systematic literature review examines how translanguaging is used in digital platforms for EFL learning, with specific attention to pedagogical practices, multimodal resources, and learner engagement. Existing research has increasingly discussed translanguaging in multilingual classrooms and digital learning environments, yet the relationship among platform use, instructional practice, multimodal meaning-making, and learner participation remains fragmented. To address this gap, the study reviewed selected articles published between 2016 and 2026 from Scopus, ERIC, ScienceDirect, SpringerLink, Taylor & Francis, and SINTA 1 and 2 journals. The review followed the principles of systematic literature review in educational research and was guided by PRISMA 2020 procedures, including identification, screening, eligibility assessment, and thematic synthesis. The findings show that digital translanguaging appears across online English teaching videos, hybrid courses, remote learning platforms, social media, AI-assisted tools, telecollaboration, and digital storytelling. Translanguaging functions as pedagogical scaffolding, interactional support, identity expression, and learner agency. The novelty of this review lies in integrating digital platforms, multimodal resources, and learner engagement into one analytical framework for understanding translanguaging in EFL learning.